Developing a Self-Assessment Guide for Undergraduates’ Report Writing - Nur Izyan Syamimi Binti Mat Hussin, Vahid Nimehchisalem, Seyed Ali Rezvani Kalajahi,; Yong Mei Fung, Shameem Rafik-Galea, Ain Nadzimah Abdullah, Sabarıah Bıntı Md Rashıd, (Opción, 2019)
Writing for academic purposes can be challenging particularly when it has to be in another language. The objective of this project was to create a useful self-assessment tool to aid ESL undergraduates in writing descriptions of tables and graphs. To meet this objective, the major areas of difficulty faced by undergraduates in presenting their research results were qualitatively explored. For this purpose, an intact group of 49 second year undergraduates was selected from a Malaysian public university. They completed an online descriptive writing task. The written samples were analyzed to find the students‟ areas of difficulty in describing tables and graphs. More specifically, the samples were analyzed for the quality of their content, organization, vocabulary, grammar, and mechanics and various problems were diagnosed. Additionally, two lecturers were interviewed with a focus on their students‟ typical problems and their expectations from the students in reporting their final year project results. Finally, in-house assessment of the developed Guide helped the researchers in its further refinement. The results of analysis of the written samples indicated that the students had difficulties in four areas which included describing the selected information, organizing the content, using the appropriate vocabulary correctly, and writing grammatically. Based on the related literature a number of ground rules were set. According to these rules and the students‟ identified areas of difficulty, a self-assessment guide was developed. The data from the interviews confirmed some of the results of the analysis of the students‟ written samples. The guide was refined based on the information provided by the lecturers in the interviews and the feedback from the in-house assessment. The guide can be introduced to students who may find it helpful in writing higher quality reports.